The mystery of the star ruby - Warner, Gertrude Chandler, 1890-1979. (Morton Grove, Ill. : A. Whitman, 2002)
The Aldens take part in a hunt at a gem mine and discover that someone is out to sabotage the contest.
500
Accelerated Reader AR